2019
DOI: 10.20944/preprints201903.0155.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating Human Photoreceptoral Inputs from Night-Time Lights Using RGB Imaging Photometry

Abstract: Night-time lights interact with human physiology through different pathways starting at the retinal layers of the eye, from the signals provided by the rods, the S-, L- and M-cones, and the intrinsically photosensitive retinal ganglion cells (ipRGC). These individual photic channels combine in complex ways to modulate important physiological processes, among them the daily entrainment of the neural master oscillator that regulates circadian rhythms. Evaluating the relative excitation of each type of photorecep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The "Cities at Night" project team has occasionally produced radiance calibrated images for scientific collaborations, and a project based at the University of Exeter is currently working on a data processing pipeline to produce a public database of calibrated images. The first mosaic of high resolution ISS images was made by Schmidt (2015), covering the administrative boundaries of the country of the Netherlands, and low resolution mosaics were made using time lapses by Sánchez de Miguel and Zamorano (2012), covering large parts of the US, Europe and middle-east.…”
Section: Night-time Astronauts Photographsmentioning
confidence: 99%
“…The "Cities at Night" project team has occasionally produced radiance calibrated images for scientific collaborations, and a project based at the University of Exeter is currently working on a data processing pipeline to produce a public database of calibrated images. The first mosaic of high resolution ISS images was made by Schmidt (2015), covering the administrative boundaries of the country of the Netherlands, and low resolution mosaics were made using time lapses by Sánchez de Miguel and Zamorano (2012), covering large parts of the US, Europe and middle-east.…”
Section: Night-time Astronauts Photographsmentioning
confidence: 99%
“…However, spectral measurements are not the easiest to obtain, especially if many of them are required. It has been shown that three bands Red, Green, Blue (RGB) photometric data can be used to determine spectral indices or photoreceptor stimuli from values recorded by a Digital single-lens reflex camera (DSLR) [17,18]. That method is much faster and easier to perform.…”
Section: Introductionmentioning
confidence: 99%
“…The imagery obtained from the International Space Station is used to estimate the spectral type of ground light sources based on colour information [ 24 ]. The colour information of DSLR cameras is also used to estimate human photoreceptoral inputs based on the spectra of standard light sources [ 25 ]. There is an increasing interest in colour detection based on single detector pointing devices as well, see, e.g., [ 26 ] and the CoSQM project ( ).…”
Section: Introductionmentioning
confidence: 99%